Selang Kepercayaan dari Parameter Distribusi Log-Normal Menggunakan Metode Bootstrap Persentil - Akhmad Fauzy (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2008)
In this article, two methods are proposed to give the interval estimation for two parameters Log-Normal distribution. We usually use traditional method to construct interval estimation. This intervalneeds a t distribution and chi-square distribution and namely traditional method. We will useanother method, namely bootstrap percentile. Bootstrap percentile method more potential inconstructing two parameters interval and give shorter interval than traditional method. This methoddoes not need an assumption that the sample has to have t and chi-square distributions.